Os estudos culturais na encruzilhada dos feminismos materiais e descoloniais - Claudia de Lima Costa (Universidade de Brasília, 2014)
In this article, I retrace the trajectory of the debates in feminist cultural studies, particularly in the United States, focusing on three types of approaches to the dichotomies reality/representation and text/context. How to grasp the materiality of th e world without giving up the fact that our narratives/representations are always already constitutive of that world? I see echoes of what material feminists advocate vis - à - vis the thorny issue of the materiality of the world in the cosmopolitical proposals advanced by Latin American decolonial feminisms. I claim that the articulation of these two projects (one derived from debates in the North and the other from the South) can serve as an inspiration to rethink – and decolonize – the practices of cultural studies in Latin America.